Comparative analysis of SMEs intensity in Ukraine and Indonesia using FIS approach - Evi Thelia Sari; Vitalli Gryga (Contemporary Economics, 2023)
The purpose of this study is to describe and examine the development of SMEs in Ukraine and Indonesia based on productivity factors of SMEs development measured SMEs contribution to the country's GDP. The study is based on data from 2000 to 2014, on number of SMEs, contribution of SMEs to GDP, labor in SMEs sectors, exports and import contributions to GDP of each country. Under complex data with uncertainty, Fuzzy Inference System (FIS) was applied to modelling process in estimating the differences between SMEs development in Ukraine and Indonesia. FIS models show the needs to improve policies on SMEs in each country of this study. We found that SMEs intensity development in Ukraine needs more SMEs to increase contribution to GDP and stipulate economic growth. While in Indonesia, growth in quantities of either labors or numbers of SMEs can be problematic, so it should focus on labors quality. Trade openness e.g., ratio export and import to GDP, shows that while Ukraine's SMEs contribution to GDP is lower, the ratio of Export and Import to GDP is increasing. Whereas Indonesia's ratio of export and import to GDP increases along with the SMEs contribution to GDP. The policies to increase the intensity development of SMEs in both countries should focus on increasing the quality of labors hired in SMEs, increasing the numbers of SMEs, reviewing and selecting the commodities that are prioritized to export and import in enhancing the ratio of export and import to GDP.
Keywords: E66; O11; 330; small and medium enterprises; SME development; trade openness; SMEs intensity; Fuzzy Inferences System